Analisa Cacat Produk Dan Kerusakan Mold Pada Proses Injection Molding Dan Tindakan Perbaikan Di PT. Patco Elektronik Teknologi - Arif, Muhammad; Windyatri, Hasyrani; ., Suhendra (Jurnal Sains dan Teknologi (JSIT), 2024)
This study examines product defects and mold damage in the injection molding process and corrective actions at PT. Patco Elektronik Teknologi. This type of research is field research with a qualitative approach. Researchers use primary and secondary data sources. Data collection techniques through observation, interviews, and documents related to product defects and mold damage in the injection molding process and corrective actions. The data were analyzed using data reduction, data presentation, and conclusion drawing methods. The results of the study show that injection molding has many advantages when compared to other plastic manufacturing methods, but in the process there are various defects in the plastic products produced. Based on the FMEA analysis, a number of product defects occur due to several factors, such as Bending, Gas Mark, Silver, Flash, Under Cut, Crack, Flow Mark, Scratches, Burn Mark, and Short Mold. Gas Mark has the highest risk priority number (RPN) value of 75. The problem of defects due to gas marks occurs in the housing panel components produced by PT. Patco Elektronik Teknologi. The company took corrective action NG Gas Mark on the housing panel product by means of mold maintenance and gas vent making by the mold shop for the cavity and ejector pin parts. After the gas vent making process was carried out, defects due to gas marks were greatly reduced in the housing panel products produced by PT. Patco.